2009
DOI: 10.1073/pnas.0905390106
|View full text |Cite
|
Sign up to set email alerts
|

Nogo receptor 1 regulates formation of lasting memories

Abstract: Formation of lasting memories is believed to rely on structural alterations at the synaptic level. We had found that increased neuronal activity down-regulates Nogo receptor-1 (NgR1) in brain regions linked to memory formation and storage, and postulated this to be required for formation of lasting memories. We now show that mice with inducible overexpression of NgR1 in forebrain neurons have normal long-term potentiation and normal 24-h memory, but severely impaired month-long memory in both passive avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
82
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 46 publications
(43 reference statements)
9
82
1
Order By: Relevance
“…This is a phenomenon that is frequently observed when comparing acute interventions with constitutive KOs where compensatory mechanisms are often activated. These results are also in line with the proposed role of NogoA and NgR1 in regulating the stabilization of neuronal circuits and in inhibiting structural rearrangements and thereby limiting, e.g., spinal cord, or ocular dominance (OD) plasticity (9,27,30,31), or regulating the formation of long-lasting memories (15).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is a phenomenon that is frequently observed when comparing acute interventions with constitutive KOs where compensatory mechanisms are often activated. These results are also in line with the proposed role of NogoA and NgR1 in regulating the stabilization of neuronal circuits and in inhibiting structural rearrangements and thereby limiting, e.g., spinal cord, or ocular dominance (OD) plasticity (9,27,30,31), or regulating the formation of long-lasting memories (15).…”
Section: Discussionsupporting
confidence: 72%
“…In ngr1 knockout (9) and in pirB knockout mice (13), ocular dominance plasticity continues after the end of the critical period, suggesting that NgR1 and PirB signaling stabilizes the neural circuitry and limits experience-dependent plasticity. In addition, NgR1 signaling can influence LTP in concert with FGF2 (14) as well as long-term memory (15).…”
mentioning
confidence: 99%
“…Additionally, downregulation of NgR1 occurs during learning, and is suggested to be required for the formation of long-term memory ( Josephson et al, 2003). Inducible overexpression of NgR1 in forebrain neurons was also recently shown to be associated with impaired long-term memory, implying a complex role for NgR1 in memory consolidation (Karlen et al, 2009). Neither NgR1 deletion nor sNgR1 treatment impaired memory function in naive or sham-injured mice in our studies, although we cannot exclude the possibility that other, more complex tests could have revealed subtle deficits in cognitive function induced by the absence of NgR1.…”
Section: Nogo-66 Receptor Inhibition After Tbi In Micecontrasting
confidence: 47%
“…(McGee et al, 2005). Interestingly, a recent study has demonstrated that NgR1 is required for lasting memories (Karlén et al, 2009). Given that LGI1 is critically important for glutamatergic synapse maturation and dendritic pruning (Zhou et al, 2009), determining whether LGI1, NgR1 and ADAM22 function collaboratively to drive synapse maturation and dendritic sculpting is a key priority for future studies.…”
Section: Discussionmentioning
confidence: 99%